Simulation of turbulent flow over hill - Tan, Elvin Zhi Wei. (2013)
A series of large-eddy simulation of turbulent flow over hill are performed with relatively coarse grid resolution to examine the effect of wind shear on aircraft. The philosophy of this computation study is to explore methods of providing a simulation that is faster, cheaper and good enough. Fluent and CDP codes are used for the tests. A circular hill model is used as the test case. The Reynolds number based on the hill height and reference velocity is predetermined as 130000, with reference to the experiment conducted by Simpson et al. [10]. A comparison of the simulation data from Fluent shows that it is capable of providing a reasonable solution that agrees with the experimental data qualitatively, for the associated flow features. CDP code, on the other hand, failed to describe the expected flow characteristics. The effect of wind shear on aircraft is then analyzed based on flight performance and aerodynamics quantities to identify potential danger flight zone associated with flow over hill. Potential danger zones are identified in the wake area, with severe wind shear, which would likely compromise flight safety for aircraft attempting to execute a landing or take-off.